The Transformation of Teacher Performance: Mapping on the Effect of Training, Motivation, and Organizational Culture - Tsuroya, Nabeela Himmatus; Bakhri, Syaiful (AL-IDARAH: JURNAL KEPENDIDIKAN ISLAM, 2023)
Teacher is one of the determining factors for the success of an education. In this case, teacher is assigned to educate the life of the nation. Many factors affect teacher performance. In this study, researchers focused on aspects of training, motivation, and organizational culture because they are relevant to the problems that exist at SDN Ngaliyan 01 Semarang. This study aims to determine: 1) the effect of training on teacher performance at SDN Ngaliyan 01 Semarang, 2) the effect of motivation on teacher performance at SDN Ngaliyan 01 Semarang, 3) the effect of organizational culture on teacher performance at SDN Ngaliyan 01 Semarang. This research used quantitative research method by involving a population of 32 teachers. The questionnaire was prepared using a Likert scale of 1-5. The method of analysis in this study used Structural Equation Modeling (SEM) – Partial Least Square (PLS) through SmartPLS 4 software. The results of the analysis of the data obtained are training did not have a significant effect on teacher performance at SDN Ngaliyan 01 Semarang because the tStatistic value was 0.420 <1.96 and P values 0.675 > 0.05, while motivation has a significant effect on teacher performance at SDN Ngaliyan 01 Semarang with tStatistic value 2.209 > 1.96 and P Values 0.029 < 0.05, and organizational culture has a significant effect on teacher performance at SDN Ngaliyan 01 Semarang with tStatistic value 3.008 > 1.96 and the value of P Values 0.003 < 0.05. The suggestions that can be given are the school leaders should conduct training of teacher performance, increase and maintain intrinsic and extrinsic motivation so that teacher performance is improved, maintain and improve organizational culture and service to customers, and minimize individualism and seniority among teachers so as not to affect their performance.